Long term Performance of 12 Species of Indian Timbers Treated with CCA in Cochin Harbour - Rao, M.V.; Cherian, C.J.; Cheriyan, P.V. (Fishery Technology, 2025)
Performance of 12 common timbers (Alstonia kurzi, Bombax insigne, Albizzih sp., Tetmmeles nudiflora, Pinus roxburghii, Polyalthikz fragruns, Shorea robusta, Terminalia paniculata, Pterocarpus dalbergioides, Dipterocarpus indicus, Tectona grandis and Xylia xylocarpa) treated with Copper- Chrome-Arsenic (CCA) at 16 kg/m3 (AI series) and 32 kg/m3 (A2 series) absorptions and exposed in the Cochin Harbour waters along with untreated ones is presented. The results show that (1) CCA treatment has greatly enhanced the durability of all the 12 species, (2) T. nudyflora, P. roxburghii, D. indicus and T. grandis of A2 series suffered only 50% to 97% destruction at the end of 22 years (3) performance of timbers in A2 series in superior to that in A1 series in most of the cases, and (4) treated nondurable species like T. nudiflora and P. roxburghii exhibited better life or borer resistance than treated durable timbers such as P. dalbergioidess, T. gmndis and X. xylocarpa.